مستوي الكفايات الواجب توافرها لدي الدارسين في قسم التربية الخاصة بجامعة طيبة للقيام بتعليم ذوي الإعاقة البصرية - الخالدي، عادل بن عابد بن حسين (جامعة طيبة - كلية التربية, 2019)
هدفت هذه الدراسة إلى تعرف مستوي الكفايات الواجب توافرها لدى طلاب وطالبات قسم التربية الخاصة بجامعة طيبة لتعليم ذوي الاحتياجات الخاصة من فئة الإعاقة البصرية في ضوء بعض المتغيرات الديموغرافية: (الجنس، والتخصص الدقيق، ودراسة جميع مقررات الإعاقة البصرية الاختيارية في مرحلة الإعداد العام). استخدم الباحث لتحقيق هذا الهدف استبانة مكونة من (28) عبارة لتحديد مستوي الكفايات الواجب توافرها لدى الدارسين. وتكونت عينة الدراسة من (160) طالبا وطالبة في مرحلة البكالوريوس في الفصل الدراسي الثاني من العام الدراسي 1438/ 1439ه. كما تمت معالجة البيانات إحصائيا باستخدام المتوسطات الحسابية، والانحرافات المعيارية، واختبار (ت)، واختبار تحليل التباين الأحادي (One-way ANOVA)، واختبار (شيفيه) للمقارنات البعدية المتعددة. وقد أشارت نتائج الدراسة إلى أن مستوى الكفايات لدى أفراد الدراسة من الطلاب والطالبات كان في المستوى المتوسط، كما أشارت إلى وجود فروق ذات دلالة إحصائية في مستوي الكفايات تعزى لمتغير التخصص الدقيق، وكانت هذه الفروق لصالح المتخصصين في الإعاقة العقلية. كذلك وجدت فروق ذات دلالة إحصائية تعزى لمتغير دراسة جميع مقررات الإعاقة البصرية الاختيارية، وكانت هذه الفروق لصالح من درسوا هذه المقررات جميعها، بينما لم توجد فروق ذات دلالة إحصائية تعزى لمتغير الجنس. وقد أوصت الدراسة بإدراج مقررات إجبارية متخصصة في الإعاقة البصرية عند بناء خطط دراسية جديدة لبرامج إعداد معلم التربية الخاصة، وعقد دورات تدريبية مكثفة للمعلمين الذين هم على رأس عملهم ويتعاملون مع ذوي الإعاقة البصرية.
The current study aims to determine the level of competencies needed for teaching students with visual impairment among pre-service special education teachers in the Department of Special Education at Taibah University in light of some demographic variables: gender (male/ female), specific specialty (learning disability/ mental retardation/ language and communication disorders/ autism and developmental disabilities) and studying all the optional visual impairment courses at the general preparatory level (yes/ no). The researcher used a questionnaire as the study tool, which consists of (28) statements to measure the level of competencies among pre-service special teachers in teaching students with visual impairment. The study sample consisted of (160) male and female bachelor students in the second semester of the academic year 1438/ 1439 H. Arithmetic means, standard deviations, one-sample t-test, independent-sample t-test, scheffe's test and one-way analysis of variance (ANOVA) were used in data analysis. The results indicated that the level of competencies in teaching students with visual impairment among male and female pre-service teachers was in the average range. The results indicated that there were statistically significant differences in the level of competencies in teaching students with visual impairment among pre-service special education teachers due to the specific specialty variable in favor of students of mental retardation specialty and due to the variable of studying all the optional visual impairment courses in favor of those who studied all of these courses. However, there were no statistically significant differences in the level of competencies due to the gender variable. Based on the current study's findings, it is recommended to include compulsory visual impairment courses in any pre-service special education teachers’ preparation programs in the future. Moreover, intensive training courses should be held for in-service special education teachers who are currently teaching students with visual impairment.
Keywords: الكفايات المهنية -- برامج إعداد المعلم -- الجودة الشاملة -- ذوى الاحتياجات الخاصة -- طلبة الجامعات